Spectral analysis of dike‐induced earthquakes in Afar, Ethiopia. Issue 4 (9th April 2016) - Tepp, Gabrielle; Ebinger, Cynthia J.; Yun, Sang‐Ho
Abstract: Shallow dike intrusions may be accompanied by fault slip above the dikes, a superposition which complicates seismic and geodetic data analyses. The diverse volcano‐tectonic and low‐frequency local earthquakes accompanying the 2005–2010 large‐volume dike intrusions in the Dabbahu‐Manda Hararo rift (Afar), some with fault displacements of up to 3 m at the surface, provide an opportunity to examine the relations among the earthquakes, dike intrusions, and surface ruptures. We apply the frequency index (FI) method to characterize the spectra of swarm earthquakes from six of the dikes. These earthquakes often have broad spectra with multiple peaks, making the usual peak frequency classification method unreliable. Our results show a general bimodal character with high FI earthquakes associated with deeper dikes (top > 3 km subsurface) and low FI earthquakes associated with shallow dikes, indicating that shallow dikes result in earthquakes with more low‐frequency content and larger‐amplitude surface waves. Low FI earthquakes are more common during dike emplacement, suggesting that interactions between the dike and faults may lead to lower FI. Taken together, likely source processes for low FI earthquakes are shallow hypocenters (<3 km) possibly with surface rupture, slow rupture velocities, and interactions with dike fluids. Strong site effects also heavily influence the earthquake spectral content. Additionally, our results suggest a continuum of spectral responses, implying either that impulsive volcano‐tectonic earthquakes and the unusual, emergent earthquakes have similar source processes or that simple spectral analyses, such as FI, cannot distinguish different source processes. Key Points: Dike‐induced earthquakes with enhanced low‐frequency content analyzed Strong site effects alter waveform character and measured frequency content Hybrid earthquakes are indicative of shallow fault ruptures and possibly fault‐dike interactions